Design of reinforced concrete beams using eurocode 2 and bs 8110 - Wong, YongXian (2014)
Singapore is currently in the phase of transitioning from BS 8110 to Eurocode2 for building design. A detailed analysis of the impact of Eurocode 2 in the current structural design environment is needed. This report presents an evaluation of flexure design methods used in both codes for designing of reinforced concrete beams. The main purpose is to analyse the flexure behaviour of the reinforced concrete beams using design methods from both codes against experimental results. The chosen specimens were simply supported reinforced concrete beams which were given either a point load or uniformly distributed load till ultimate failure was reached.